2022
DOI: 10.1016/j.amsu.2022.103326
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous sinus thrombosis as a complication of COVID-19 infection – A case report

Abstract: Introduction and importance Severe acute respiratory distress syndrome coronavirus 2 is the causative agent of COVID-19 (Coronavirus 2019) infection. Although symptoms are usually associated with the respiratory system, its neurological involvement should not be underestimated. The most common cerebrovascular complication following the infection is ischemic stroke however, CVST (Cerebral Venous Sinus Thrombosis) has been reported. Presentation of case We report a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Poyiadji et al (13) reported the MRI findings of an adult female patient who developed acute necrotizing hemorrhagic encephalopathy associated with COVID-19. Rajbhandari et al (14) reported that cerebral sinus vein thrombosis may develop as a complication of COVID-19 infection in young patients. In a study of paediatric patients with COVID-19 infection, Sun et al (15) reported clinical conditions such as septic shock, multi-organ failure, intussusception, toxic encephalopathy, status epilepticus and disseminated intravascular coagulation as complications.…”
Section: Discussionmentioning
confidence: 99%
“…Poyiadji et al (13) reported the MRI findings of an adult female patient who developed acute necrotizing hemorrhagic encephalopathy associated with COVID-19. Rajbhandari et al (14) reported that cerebral sinus vein thrombosis may develop as a complication of COVID-19 infection in young patients. In a study of paediatric patients with COVID-19 infection, Sun et al (15) reported clinical conditions such as septic shock, multi-organ failure, intussusception, toxic encephalopathy, status epilepticus and disseminated intravascular coagulation as complications.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells can participate in the recruitment of inflammatory cells, and are themselves a significant source of pro-inflammatory cytokines. In addition, cerebrovascular thrombosis contributes to the brain hypoxic injury in some individuals with COVID-19 ( Baldini et al, 2021 ; Rajbhandari et al, 2022 ; Sashindranath and Nandurkar, 2021 ). With regards to immune system, accumulating clinical evidence shows an abnormal and uncontrolled production of cytokines (cytokine storm) in critically ill COVID-19 patients ( Hirawat et al, 2021 ; Hu et al, 2021 ; Wang et al, 2021 ).…”
Section: Necessity Of Studying Pathophysiology Of Covid-19 At a Multi...mentioning
confidence: 99%